Overconfidence Bias in Working Capital Management and Performance of Small and Medium Enterprises: The Perspectives of Ghanaian SME Managers - Asri, Marsidi; Jeff, Lamptey; Bilyaminu, Usman; Ashemi, Baba Ali; Wasilu, Suleiman (Human Resource Management Academic Research Society (HRMARS), 2020)
Although managerial overconfidence is receiving substantial attention in economic analysis, explanations so far mostly focused on corporate executives and corporate investment and financing decisions. This study investigates SME managers (owners) overconfidence behavioral bias in working capital management and performance. A qualitative case study was employed to explore the perspectives of 35 SMEs managers from trading and manufacturing firms. Data were obtained through Semi- structured interviews. Based on the thematic analysis, the study found superior financial ability, perfect industry knowledge and optimism in business success to be SMEs overconfidence behaviors and their influence on working capital management and performance resulted in aggressive working capital investment and financing and expected higher performance. Specifically, overconfident SME managers is more likely to overinvest in working capital inventory for expected higher profits if they have access to sufficient internal capital. However, they are less likely to invest more in firms with substantial working capital investment in inventories if expected sales revenue are below expectation. We argued that, overconfident matters so it is not enough to study working capital management and performance of SMEs without considering manager’s biases.